Implementation of Criminal Law to Determine Persons of Environmental Pollution and/or Destruction in Court - Rochmani Rochmani; Safik Faozi; Wenny Megawati; Dyah Listyarini (Pandecta Research Law Journal, 2023)
Pollution and/or environmental damage continues to occur and according to the Environmental Quality Index (IKLH) the environment in Indonesia is increasingly damaged and many parties are harmed both humans and the environment itself but an effective settlement of environmental cases has not been found. Thus it is necessary to think about being able to resolve environmental issues that are effective and consideratejusticethe environment itself. A good and healthy living environment should be realized. This desire can be realized by applying appropriate laws that can deter perpetrators of environmental pollution and/or destruction. The purpose of this research is; to analyze and explain the effective resolution of environmental cases that takes into account the environment itself and the application of criminal law that can deter perpetrators of environmental pollution and/or destruction. The research method used is normative legal research to find the law for an in-concocreto case. Criminal law instruments in the settlement of environmental cases in judicial practice, there are still obstacles in presenting evidence, it is still necessary to think about other issues that are not regulated in the law, especially the formulation of environmental offenses. The use of criminal law instruments is more effective because prosecutors have wider powers of coercion, for example detention, search, and faster execution. Criminal law instruments not only deter people who violate them but are also aimed at other people so they do not commit acts that violate the law if they do not want to be subject to criminal sanctions.